Detection of Actinobacillus pleuropneumoniae Infection in Pigs - Willson, Philip J. (1987)
It is difficult to control the spread of porcine haemophilus pleuropneumonia caused by Actinobacillus pleuropneumoniae because there is no sensitive and specific way to accurately determine whether or not a pig herd is infected. This paper reports bacteriological and serological techniques used to detect A. pleuropneumoniae infection in pigs from a herd with endemic disease. The bacteria were isolated from the anterior nasal mucosa of grower pigs, but not from younger or older pigs. Bacteriological culture of several tissues from the respiratory tract showed that nine of ten young finishing pigs were infected, but culture of lung tissue from slaughtered hogs detected infection in only 39 of 288 (13.5%). Both cooler storage temperature and use of selective medium prolonged the time that lung tissue could be stored and the organism still recovered. An enzyme-linked immunosorbent assay detected serotype-specific antibodies in serum of infected pigs.